Efforts of Guidance and Counseling by Bhabinkamtibmas to Prevent Child Molestation in Grobogan Police Jurisdiction. - Magenda Dimas Andrianto (Akademi Kepolisian Republik Indonesia, 2023)
Disturbances of public security and order are divided into three, namely potential disturbances, thresholds of disturbances, and real disturbances. The number of disturbances resulted in not conducive public security and order. Child molestation in the jurisdiction of Grobogan Regional Police increased from 2019 to 2022. This resulted in not conducive public security and order in the jurisdiction of the Grobogan Police Station. Preventive efforts carried out by Grobogan Regional Police in overcoming child abuse are still not effective, so more preventive efforts are needed against child abuse through Bhabinkamtibmas counseling guidance. Bhabinkamtibmas as a police officer in a village or village becomes the front line in the community. Therefore, Bhabinkamtibmas has an important role through counseling guidance on the prevention of child abuse. The purpose of this study was to determine the organizational resources and management system of Bhabinkamtibmas counseling guidance on the prevention of child abuse at the Grobogan Police Station. This study used qualitative research by taking data conducted through interviews, observations, and document studies. The results of this study show that Bhabinkamtibmas counseling guidance has not been optimal so that more efforts are needed to prevent child abuse in terms of human resources, money, facilities and infrastructure, and methods as well as planning, organizing, implementing, and supervising and controlling. This is done so that public security and order at the Grobogan Police Station are conducive and the community can feel safe, comfortable, and peaceful.